Modeling and control of two five-phase induction machines connected in series powered by matrix converter - Mohamed Nekkaz; Abdelkader Djahbar; Rachid Taleb (Institute of Advanced Engineering and Science, 2021)
The two five-phase Induction Motor (IM) drive system that is serially connected is available in literature. The power supply of such system is considered as a matrix converter (a direct AC to AC converter system) by three and five-phases outputs. The main benefit from the drive topology is the sinusoidal source as a side current with a controllable input side power factor. The decoupled control is achieved similarly to the inverter based drive system. In this paper; the decoupled control of two five-phase induction machines serially connected and powered by a five-phase matrix converter as well as analytical and simulation results are presented.